Does slow motion impact on the perception of foul play in football? - Spitz, J.; Put, K.; Wagemans, J.; Williams, A. M.; Helsen, W. F. (European Journal of Sport Science, 2017)
Objectives: Slow-motion replays of foul play situations are now used in the education and training of sports officials. We investigated the impact of video speed on the decision-making process of association football referees and how this interacted with expertise. Methods: Three different groups of referees, varying in level of expertise, assessed video clips from an in-game perspective. Video clips represented corner kick and open play situations in which a foul occurred or not. For these foul/no foul situations, the referees had to make a technical (no foul; indirect free kick; direct free kick; or penalty kick) and a disciplinary decision (no card; yellow card; or red card), under both slow-motion and real-time viewing conditions. Accuracy scores were determined by comparing participant`s responses with the decisions of an expert panel. Results: Significant differences were observed across groups for foul/no foul situations, suggesting that the experts were able to process the available information more effectively than their less expert colleagues. The accuracy scores for the technical decision were higher in slow motion (67%) compared to a real-time viewing condition (56%), particularly for corner kick situations. No differences were found between real time and slow motion for the disciplinary decision. Conclusions: Slow-motion footage results in higher accuracy scores for complex technical decisions. These findings have implications for the use of slow-motion replays in the decision-making process of referees.